Polish Independent Press Summary, no. 15 (1988) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
A digest of Polish underground press (including articles, tables of content, and book covers) compiled by members of the RFE Polish Underground Publications Unit to be used in a daily 20-minute broadcast on Polish samizdat. Extract from Przegląd Wiadmości Agencyjnych, no. 46 (30 December 1987). Extract from CDN - Głos Wolnego Robotnika, no. 218/219 (17 December 1987). Extract from Samorządna Rzeczposolita, no. 20 (14 December 1987). Extract from Horyzont, no. 6 (20 December 1987). Extract from Solidarność Walcząca, no. 24 (13-27 December 1987). Extract from Solidarność Walcząca, no. 25 (25 December 1987-10 January 1988). Extract from Solidarność Walcząca - Poznań, no. 79 (18 Devember 1987). Extract from Wiadomości, no. 263 (13 December 1987). Table of Contents from Krytyka, no. 25 (1987). Extract from Krytyka, no. 25 (1987). Table of Contents from Czas Kultury (1987). Table of Contents from Czabański, Krzysztof. Marzec 1981 - Bydgoszcz. Warszawa: Niezależna Oficyna Wydawnicza i Archiwum Solidarności, 1987.